Kewenangan International Criminal Court dalam Penanganan Kasus Dugaan Kejahatan terhadap Kemanusiaan oleh Rodrigo Duterte - Maria Merry De Angel Putri; Dhesy A. Kase; Gerald A. Bunga (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the jurisdiction of the International Criminal Court (ICC) in addressing alleged crimes against humanity related to the War on Drugs policy under the leadership of Rodrigo Duterte. This research employs a normative juridical method with statute, case, and comparative approaches, supported by library research using primary, secondary, and tertiary legal materials. The findings indicate that the ICC retains jurisdiction under the Rome Statute 1998, particularly through ratione materiae, ratione temporis, and ratione personae. The Philippines’ withdrawal from the Rome Statute in 2019 does not eliminate ICC jurisdiction over crimes committed prior to withdrawal, as stipulated in Article 127(2). The War on Drugs policy fulfills the elements of crimes against humanity due to widespread and systematic attacks against civilians, supported by extrajudicial killings and ineffective national law enforcement. The principle of complementarity demonstrates a condition of state unwillingness, positioning the ICC as a court of last resort. This study concludes that the ICC’s jurisdiction in this case is legally justified and plays a crucial role in ensuring accountability and preventing impunity in international law.